»Where Do All the Calculators Go?« Methodological Considerations about How to Think about Robots and their Afterlife - Tretter, Max (Instrumente Gottes. Soziale Roboter und KI-Tools in religiösen Kontexten, 2025)
“Where do all the calculators go?” Starting from this question and noting that the afterlife of robots is a theme frequently explored in popular culture yet seldom addressed in academia, this article investigates whether it is possible to address such questions in a methodologically plausible and scientifically comprehensible manner. In this paper, I present and critically evaluate three distinct approaches, each designed to enable scholarly investigation—compliant with academic standards—into the sample question of whether an afterlifeafterlifeafterlifefor robots exists, or whether it is plausible to assume its existence: 1) 1)a philosophical–theological approach that explores the properties of robots and their theological significance, 2) a psychological–theological approach that considers the possibilities of artificial spirituality, and 3) a Biblical–theological approach that enquires into the eschatological whereabouts of all creation.</
Keywords: Systematic Theology; eschatology; robot theology; artificial intelligence